International Unionism: A Study in Canadian-American Relations - Crispo, John H. G. (McGraw-Hill of Canada, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive examination. While a fair amount has been written about this unusual phenomenon, little of this material is very complete or incisive. As a result the door has been left open for those with an axe to grind to express themselves freely on the subject without the fear of contradiction based on cold hard facts. This study may reduce the frequence of such utterances in the future. It endeavours to deal objectively with an area of Canadian-American relations where emotions and prejudices have distorted public debate. Many of the events which have provided fuel for this debate over the past few years are dealt with, including the Seafarers' International Union dispute on the Great Lakes and the Internaitonal Typographical Union strike againist the three Toronto newspapers. –Preface. Contents: Introduction (pages 1-10) – Explaining the presence of international unionism in Canada (pages 11-49) – The Canadian membership within international unions (pages 50-95) – Relations between the central federations of labour in Canada and the United States (pages 96-145 – The unity and structure of the Canadian labour movement /(pages 146-178) – Collective bargaining policies and practices in Canada (pages 179-230) – Policies and practices outside the area of collective bargaining (pages 231-258) – The flow of funds and benefits across the border (pages 259-278) – Employer and government attitudes towards international unionism (pages 279-301) – Summary and conclusion (pages 302-324) – A selected bibliography (pages 325-327).
OCLC: 232617

The Role of International Unionism in Canada - Crispo, John H. G. (Canadian-American Committee, 1967)
The relationship between the Canadian and American labour movements is unique. It has given rise to considerable controversy and yet has been the subject of surprisingly little intensive research. As a result those with an axe to grind have been able to express themselves without fear of contradiction based on cold, hard facts. This study may reduce the frequency of such utterances. It endeavors to deal objectively with an area of Canadian-American relations where emotion and prejudice have distorted public debate. The reader will have to judge for himself whether sufficient detachment has been shown to achieve real objectivity. –From author's preface
Keywords: Labor unions – Canada